2003
DOI: 10.1177/13684302030063003
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Friends or Members of a Group? Sex Differences in Relational and Collective Attachment to Groups

Abstract: In the current investigation, we studied sex differences in belonging needs by exploring men's and women's attachment to groups. Previous work has shown that women's social needs tend to be expressed in terms of relational bonds, whereas men's also have a strong collective component (e.g. Gabriel & Gardner, 1999). In this research, we asked men and women to consider one of their important group memberships and to complete Prentice, Miller, and Lightdale's (1994) group attachment scales. In two studies, finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 21 publications
5
32
0
1
Order By: Relevance
“…Consequently, collectivists tend to emphasize group needs over individual needs. This type of relationship-focused group orientation of collectivists is consistent with past research which found that collectivists tend to place greater value on relatedness, interdependence and in-group identification than individualists (Seeley et al, 2003;Triandis, 1995). Further evidence suggests that members of collectivist cultures frequently cooperate in groups, especially when they are working with their in-group (e.g., close associates, Earley, 1993) but that members of individualist cultures showed a marked tendency to avoid cooperation (Kirkman and Shapiro, 2001;Leung & Bond, 1984).…”
Section: The Role Of Boundary Peremeabilitysupporting
confidence: 76%
“…Consequently, collectivists tend to emphasize group needs over individual needs. This type of relationship-focused group orientation of collectivists is consistent with past research which found that collectivists tend to place greater value on relatedness, interdependence and in-group identification than individualists (Seeley et al, 2003;Triandis, 1995). Further evidence suggests that members of collectivist cultures frequently cooperate in groups, especially when they are working with their in-group (e.g., close associates, Earley, 1993) but that members of individualist cultures showed a marked tendency to avoid cooperation (Kirkman and Shapiro, 2001;Leung & Bond, 1984).…”
Section: The Role Of Boundary Peremeabilitysupporting
confidence: 76%
“…The framework sees relational competence as a basic driver of why some entrepreneurs are capable of creating access to the resources needed to make a stepchange, whereas others are not. Such relational competences seem not equally divided across the two sexes in that they are also shaped by genetics (Baron-Cohen, 2002;Seeley, Gardner, Pennington, & Gabriel, 2003). Research has shown that, compared to men, women relate less often to highly abstract entities, such as groups, institutions, and organizations (Baumeister & Sommer, 1997;Gabriel & Gardner, 1999) because they are less equipped in predicting the behavior of systems (Baron-Cohen, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the present study, we found no gender differences, neither in self-construal nor in type of identifi cation. Seeley, Gardner, Pennington, and Gabriel (2003) investigated a similar gender difference hypothesis using Prentice et al's (1994) common bond and common identity subscales. Consistent with the current results, Seeley et al also did not fi nd signifi cant gender difference.…”
Section: Gender Differences In Types Of Identifi Cationmentioning
confidence: 99%